On the Pull-Out Behavior of Hooked-End Shape Memory Alloys Fibers Embedded in Ultra-High Performance Concrete - Akbari Baghal, Amir Ebrahim; Maleki, Ahmad; Vafaei, Ramin (International Journal of Engineering and Technology Innovation, 2021)
This study presents a three-dimensional non-linear finite element investigation on the pull-out behavior of straight and hooked-end Shape Memory Alloys (SMA) and steel fibers embedded in Ultra-High Performance Concrete (UHPC) using a single fiber pull-out model. A bilinear cohesive zone model is used to characterize the interfacial traction separation relationships. The Concrete Damage Plasticity (CDP) model is used to simulate UHPC, and the mechanical behavior is obtained through experimental tests. Parametric studies are conducted to evaluate the effects of fiber materials, fiber diameters, and hook angles on the load-displacement behavior. A good agreement between the numerical and experimental results is obtained. It is found that the hooked-end fibers with a smaller diameter and a hook angle of 40° can be a better choice for structural application. Furthermore, it is observed that the use of SMA fibers significantly improves the pull-out performance between fibers and UHPC.